Africa's Mineral Fortune : The Science and Politics of Mining and Sustainable Development - Ali, Saleem H.; Sturman, Kathryn; Collins, Nina; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
For too long Africa's mineral fortune has been lamented as a resource curse that has led to conflict rather than development for much of the continent. Yet times are changing and the opportunities to bring technical expertise on modern mining alongside appropriate governance mechanisms for social developmentare becoming more accessible in Africa. This book synthesizes perspectives from multiple disciplines to address Africa s development goals in relation to its mineral resources. The authors cover ways of addressing a range of policy challenges, environmental concerns, andpublic health impacts and also consider the role of globalization within the extractive industries. Academic research is coupled with key field vignettes from practitioners exemplifying case studies throughout. The book summarizes the challenges of natural resource governance, suggesting ways in which mining can be more effectively managed in Africa. By providing an analytical framework it highlights the essential intersection between natural and social sciences, central to efficient and effective harnessing of the potential for minerals and mining to be a contributor to positive development in Africa. It will be of interest to policy makers, industry professionals, and researchers in the extractive industries, as well as to the broader development community.
INTRODUCTION -- --Saleem H. Ali and Kathryn Sturman -- Part I: The Politics of African Mining -- Chapter 1: --Harmonizing African Resource Politics? Lessons from the African Mineral Development Centre -- --Rodger Barnes, Kojo Busia and Marit Kitaw -- Chapter 2: --Taking Account of Conflict Risks in Africas resource governance -- --Kathryn Sturman and Fitsum Weldegiorgis -- Chapter 3:-- Chinese Mining in Africa and its Global Controversy -- --Barry Sautman and Yan Hairong -- Chapter 4:-- Field Vignette. Moving from Prescriptive to Performance Based Regulation: The Case of Waste Management -- --Andy Fourie, Mwiya Songolo and James McIntosh -- Chapter 5:-- Field Vignette. Ghanas Policy on Artisanal and Small-scale Mining -- --Benjamin Aryee -- Part II: Data and Models: Supporting Strategic Planning for Africas Minerals -- Chapter 6:-- Developing accurate and accessible geoscience data for sustainable mining in Africa -- --Judith Kinnaird and Raymond Durrheim -- Chapter 7:-- Challenges in Measuring the Local and Regional Contributions of Mining: Lessons from Case Studies in Rwanda, Zambia and Ghana. -- --Julia Horsley and Shabbir Ahmed -- Chapter 8:-- Measuring Transformative Development from Mining: A case Study of Madagascar -- --Fitsum Weldegiorgis and Cristian Parra -- Chapter 9:-- Field Vignette. The Extractives Dependence Index and its Applications to Africa -- --Degol Hailu, and Chinpihoi Kipgen -- Chapter 10:-- Field Vignette. The West African Exploration Initiative (WAXI) -- --M.W. Jessel and WAXI Team -- Part III: Environment, Health and Innovation -- Chapter 11: --Africas mineral and biodiversity wealth: Approaches to reduce conflict between extractive development and environmental conservation -- --Mahlette Betre, Marielle Canter Weikel, Romy Chevallier, Janet Edmond, Rosimeiry Portela, Zachary Wells, and Jennifer Blaha -- Chapter 12: --Ebola and emerging infections: Managing risks to the mining industry -- --Osman A Dar, Francesca Viliani, Hisham Tariq, Emmeline Buckley, Abbas Omaar, Eloghene Otobo and David L. Heymann -- Chapter 13: --Mineral investment decision making in Africa: A real options approach in integrating price and environmental risks -- --Kwasi Ampofo and Alidu Babatu Adam -- Chapter 14: --The potential of Zambian Copper-Cobalt metallophytes for phytoremediation of minerals wastes -- --Antony van der Ent, Peter Erskine, Royd Vinya, Jolanta Mesjasz- Przybyowicz) and Franois Malaisse -- Chapter 15:-- Field Vignette. South Africas Underground Women Miners -- --Asanda Benya, -- Chapter 16:-- Field Vignette. Sapphire mining, water and womens health -- --Lynda Lawson -- Part IV: Reconciling Scales of Mining Governance -- Chapter 17: --Strategies for working with artisanal and small-scale miners in sub-Saharan Africa -- --Nina Collins and Lynda Lawson -- Chapter 18:-- Community health, safety and sanitation: considering localized governance and monitoring of water quality -- --Danellie Lynas and Gernelyn Logrosa and Ben Fawcett -- Chapter 19: --Gauging the effectiveness of certification schemes and standards for responsible mining in Africa -- --Renzo Mori Junior -- Chapter 20:-- Field Vignette. Sourcing Conflict Free Minerals from Central Africa -- --Stephen B. Young -- Chapter 21:-- Field Vignette. The Australia-Africa Minerals and Energy Group (AAMEG) -- --Trish OReilly -- CONCLUSION: --Beyond African Exceptionalism in Harmonising Science and Politics for Development -- --Kathryn Sturman and Saleem H. Ali
Includes bibliographical references and index.
Also available in print format.
Keywords: Mineral industries -- Environmental aspects -- Africa; Mineral industries -- Government policy -- Africa; Mines and mineral resources -- Africa; Electronic books